Analysis of adherence to postpartum screening for early dysglycemia in women with previous gestational diabetes - Cvijanović, Sara; Lalić, Nebojša; Stoiljković, Milica (Medicinski podmladak, 2025)
Introduction: Previous studies have shown that women with gestational diabetes (GD) are at higher risk for residual postpartum dysglycemia. Nevertheless, adherence to early postpartum screening among women with previous GD is extremely unsatisfactory.Aim: Analysis of clinical, anthropometric and sociodemographic characteristics of women with previous GD who were screened during the early postpartum period for residual dysglycemia.Material and Methods: 102 pregnant women with GD were divided into groups based on the early postpartum screening for dysglycemia: group A, screened (n=19), and group B, not screened (n=83). We analysed age, body mass index (BMI), parity, smoking habits, having GD in previous and gestational hypertension in the current pregnancy, family history of type 2 diabetes (T2D), glycemic parameters (fasting glucose (FG) and HbA1c in the 2nd and 3rd trimester), therapeutic regimen, number of endocrinology outpatient visits and hospitalizations, pregnancy outcomes and results of screening oral glucose tolerance test using appropriate statistics.Results: Postpartum screening was conducted in 18.6% (group A), among whom prediabetes was diagnosed in 26.3% of women with previous GD. Women in group A were older (36.21±5.05) than in group B (33.48±5.57years, p=0.047). Groups did not differ regarding preconception BMI (A: 28.03±5.69 kg/m² vs B: 28.17±6.84 kg/m², p=0.971), in second and third trimester FG*- (A: 4.64±0.92 mmol/L vs B: 4.62±0.77 mmol/L, p=0.953; A: 4.61±0.73 mmol/L vs B: 4.91±1.02 mmol/L, p=0.507, respectively) and HbA1c (A: 5.06±0.40% vs B: 5.18±0.64%, p=0.621; A: 5.30±0.34% vs B: 5.25±0.54%, p=0.690, respectively). On the other hand, women in group A (3.57±1.51) more frequently attended outpatient endocrinology examinations than women in group B (2.68±1.16, p=0.028). Conclusion: Our results implied very low adherence to early postpartum screening, while women with previous GD who underwent early postpartum screening for residual dysglycemia were older and had more frequent ambulatory endocrinology visits during pregnancy.
Keywords: screening adherence; gestational diabetes; early postpartum dysglycemia